THE USE OF COLLABORATIVE STRATEGIC READING (CSR) TO IMPROVE STUDENTS’ READING COMPREHENSION IN THE SECOND GRADE STUDENTS OF SMP NEGERI 2 TARAKAN - Sawitri, Era (Borneo Journal of English Language Education, 2019)
The purpose of this study was to look for the effectiveness of using collaborative strategic reading technique to improve reading comprehension of second grade students at SMP Negeri 2 Tarakan. This?? research??? was ??Quasi-Experimental??? design.??? Purposive??? sampling technique? was used to collect the sample.? There were? two classes? obtained? as samples in this research, they were experimental class and control class. Experimental class (VIII C) was treated by using collaborative strategic reading technique. Control class (VIII A) was treated by using cooperative learning technique.? Each? class? consisted? of? 32? students? of? SMP? Negeri? 2? Tarakan? in academic year 2018/2019. The instrument of this research was reading tests that consisted of pre-test and post-test. In analyzing the data, the researcher used an independent sample t-test in the SPSS v.24.0. The? results? show? that there? were? significance? difference? in the students? score of experimental class and the control class. This is indicated by the students? mean score of pretest and posttest. The mean score of the experimental class in pretest was 40.50 and in posttest was 71.75. It was indicated that the mean score in the experimental class has increased to 31.25. The mean score of the control class in pretest was 44.38 and in posttest was 64.13. It was indicated that the mean score in the control class has increased to 19.75. It is proven that the results of the experimental?? class?? were?? higher?? than?? the?? control?? class.?? Results?? from?? the independent sample T-test and T-table from pretest was 1.117 and posttest was 2.335 and the T-table was 1.998 or in pretest was 1.117 < 1.998 and in posttest was 2.335> 1.998. In other words, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The results of data analysis proved that the results? of teaching? reading? comprehension? by using? collaborative? strategic reading technique was higher than by using cooperative learning technique. Based on? the? explanation? above,? it? can? be? concluded? that? the? collaborative? strategic reading?? technique?? was? more?? effective?? than? by? using?? cooperative?? learning technique.